Bone SPECT–CT: An additional diagnostic tool for undiagnosed wrist pain. Issue 10 (October 2016) - Shirley, R.A.; Dhawan, R.T.; Rodrigues, J.N.; Evans, D.M.
Summary: Diagnosis of wrist pain can be difficult to determine with clinical examination and conventional imaging techniques alone. Bone SPECT–CT (single-photon emission tomography with computerized tomography) is a hybrid imaging technique that overlays functional bone scintigraphy in tomographic/3D mode with conventional CT. Data from the two modalities are complementary; areas of abnormal bone metabolism can be localized with anatomical precision, hitherto lacking in conventional bone scans, while structural information from the CT scan further embellishes the diagnostic information. Over the last 6 years, one surgeon (David Evans) has used bone SPECT and later bone SPECT–CT as an additional line of investigation. This is a series of 21 consecutive patients with wrist pain that could not be diagnostically resolved with the usual combination of history, examination, and conventional imaging, and therefore underwent bone SPECT–CT. Clinical and imaging findings, management, and outcomes of these cases are discussed to explore the potential role of this hybrid functional modality in hand and wrist surgical practice.